2011
DOI: 10.1177/2042098611400332
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of deprescribing

Abstract: Abstract:Objective: Polypharmacy and adverse drug reactions are frequent and important among older people. Few clinical trials have evaluated systematic withdrawal of medications among older people. This small, open, study was conducted to determine the feasibility of a randomized controlled deprescribing trial. Methods: Ten volunteers living in the community (recruited by media advertising) and 25 volunteers living in residential aged-care facilities (RCFs) were randomized to intervention or control groups. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 23 publications
2
51
0
1
Order By: Relevance
“…This reduction was primarily seen amongst medications for primary prevention. These results are consistent with other studies in frail elderly patients in other healthcare settings [20][21][22]. A program to address polypharmacy in elderly community dwelling patients resulted in an average decrease of 4.4 medication per patient [21] whereas an intervention in a geriatric specialty hospital decreased medications by 47% (2.8) per patient [20].…”
Section: Discussionsupporting
confidence: 82%
“…This reduction was primarily seen amongst medications for primary prevention. These results are consistent with other studies in frail elderly patients in other healthcare settings [20][21][22]. A program to address polypharmacy in elderly community dwelling patients resulted in an average decrease of 4.4 medication per patient [21] whereas an intervention in a geriatric specialty hospital decreased medications by 47% (2.8) per patient [20].…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have shown that systematic deprescribing may be feasible [6][7][8][9], however, the translation of these into practice may be limited due to multiple barriers. General practitioners have reported that a major barrier to optimising medication use is patient resistance to have a medication ceased [10].…”
Section: Introductionmentioning
confidence: 98%
“…3 This is further supported by a recent Australian pilot study which confirmed the feasibility of deprescribing in polypharmacy. 4 …”
Section: Polypharmacymentioning
confidence: 99%